STRATEGY FOR CHARACTER FORMATION OF CHILDREN IN THE FAMILY ENVIRONMENT: ISLAMIC EDUCATION PERSPECTIVE - Choli, Ifham; Rahma, Etika Nailur; Zumrud, Azzah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
Character education is a conscious and planned effort to educate students to understand and practice moral values, ethics, and noble character in everyday life. Character education is not just teaching about good and bad but is a process of forming values that include cognitive, affective, and psychomotor dimensions. The family is the first and foremost place for the formation of a child's character. If you want to form a child with good character, it must start from the family. This research is a literature study that aims to examine Character Formation that must be carried out in the family. Literature research activities are carried out by collecting data from various literature. Character education is the main pillar in the formation of a child's personality from an early age. Character not only reflects external behavior but also reflects moral and spiritual values embedded in the soul. In Islam, character formation has a strong basis from the Qur'an and the Sunnah of the Prophet Muhammad SAW, which emphasizes the importance of noble morals as a reflection of a person's faith applied, such as role models, habits, advice, dialogue, and reward and punishment systems. These methods are not only effective in the family environment, but also in schools. The function and purpose of character education is to form a generation that is not only intellectually superior but also ethical, responsible, and able to make a positive contribution to community life.